FACTORS THAT INFLUENCE THE INTEREST OF STUDENTS IN SAVING AT SMK NURUL FINANCIAL INSTITUTIONS OF NURUL ABROR AL-ROBBANIYIN ISLAMIC BOARDING SCHOOL - Faiqoh Nur (Al-Qalam Institute, Probolinggo, East Java, Indonesia, 2023)
Both conventional and sharia financial institutions provide saving services for customers. Various products and service systems are designed and structured by the institution in such a way as to generate public interest in saving and generate customer satisfaction. That's because saving is an important need for many people who need an agency to manage it properly. This study aims to find out what motives encourage customers to put their trust in saving a certain amount of money at the SMK NAA Financial Institution. The research methodology used in this paper is a qualitative case study approach with descriptive data. Existing data obtained from informants with sampling techniques. The results of this study indicate several factors that motivate customers to save, including: having remaining pocket money, awareness of future needs and the influence of the surrounding environment. And also shows the factors that become obstacles to saving, including: lack of promotion, poor service and economic limitations.